THE USE OF BASEL SCORE IN EARLY DETECTION OF CORONARY LESION SEVERITY IN NON-ST SEGMENT ELEVATION MYOCARDIAL INFARCTION AND UNSTABLE ANGINA PECTORIS - Andrew Eka Pramudita Sunardi; Dewi Utari Djafar; Edmond Leonard Jim; Fima Lanra Fredrik Gerald Langi (JURNAL WIDYA MEDIKA, 2023)
Early diagnosis of cardiac ischemia is crucial for effective management of acute myocardial infarction. The BASEL (Better Analysis of ST-segment Elevations and Depressions in a 12-leads-ECG) score has been shown to provide additional diagnostic value to the established electrocardiographic (ECG) criteria. This study aimed to evaluate the use of BASEL score to determine the severity of coronary lesions in patients with non-ST segment elevation acute coronary syndrome. This study used a cross-sectional approach and was conducted from January 2021 to January 2022. From a total of 90 subjects, more than three-quarters were male, while the mean age was 60.3 years. The median BASEL score was 2.3 (1–4.2). GRACE 2.0 score had a mean of 97.3±26. The SYNTAX I score had a mean of 25±15.6, the SYNTAX II – PCI median score was 34.5 (25.9-42.4), and the SYNTAX II-CABG mean score was 23.4±11.9. The BASEL score showed a significant association with the SYNTAX I score both in univariate 2.60 (2.60-3.59), p